Exploration Germplasm of Tobacco In East Java - Ismul Mauludin Al Habib; Fatimatuz Zuhro (BIO-CONS : Jurnal Biologi dan Konservasi, 2021)
Conservation of germplasm is absolutely necessary in order to repair a plant species. The first step in order to get the desired genetic properties is by germplasm exploration. The aim of this research was to get the germplasm of tobacco in East Java. Exploration was conducted in July, August and September 2018 in East Java. Determination of appropriate areas for exploration based on the result of discussion and suggestions from Department of Agriculture and leader in that community. The activity of exploration was conducted by researchers by come in the crop location directly. The result of this exploration showed that; (1). There are 16 types of tobacco in 6 districts of East Java province, among others; Krosok, Kasturi, Burley, Benyak, Semporis, Moris DB, Besuki, Tambeng, Kayu Mas, Mersi, BB, K3 19, Jowo, Krempol Jati, Prancak 95 and Jepon Raja, (2). There are similar types of tobacco in 2 districts (Probolinggo and Jember), namely Kasturi tobacco. This is related to the spread of demand for tobacco processing companies and exporters, as well as the geographical location of the region.